Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.21037/atm-22-393
|View full text |Cite
|
Sign up to set email alerts
|

RAF1 mediates the FSH signaling pathway as a downstream molecule to stimulate estradiol synthesis and secretion in mouse ovarian granulosa cells

Abstract: Background: The v-raf-leukemia viral oncogene 1 (RAF1) plays an essential physiological role in reproduction and development through the mediation of steroid hormone synthesis. Follicle-stimulating hormone (FSH) signaling pathway was not involved in the majority of RAF1 studies, whether RAF1 takes part in the signaling events of gonadotropic hormones such as FSH in ovarian tissue is unknown. Methods:The process is blocked by treating granulosa cells (GCs) with the RAF1 inhibitor, RAF709.Inhibition of RAF1 acti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 40 publications
(39 reference statements)
0
1
0
Order By: Relevance
“…V-RAF-leukemia viral oncogene 1 (RAF1) is the core member of the RAS/RAF/MEK/ERK signaling pathway and has been approved to play an essential role in reproduction and development by regulating steroid hormone synthesis ( 35 , 36 ). Through in vitro and in vivo studies, Luo et al ( 37 ) found that RAF1 could stimulate E2 synthesis and secretion through the FSH signaling pathway in mouse granulosa cells. Nonetheless, the role of RAF1 in ovarian function and follicular development of poultry has been largely understudied.…”
Section: Discussionmentioning
confidence: 99%
“…V-RAF-leukemia viral oncogene 1 (RAF1) is the core member of the RAS/RAF/MEK/ERK signaling pathway and has been approved to play an essential role in reproduction and development by regulating steroid hormone synthesis ( 35 , 36 ). Through in vitro and in vivo studies, Luo et al ( 37 ) found that RAF1 could stimulate E2 synthesis and secretion through the FSH signaling pathway in mouse granulosa cells. Nonetheless, the role of RAF1 in ovarian function and follicular development of poultry has been largely understudied.…”
Section: Discussionmentioning
confidence: 99%